Positioning PELA practice within language and literacy development - Veitch, Sarah; Johnson, Stephen (Journal of Academic Language and Learning, 2022)
Post-entry language assessment (PELA) is commonplace in Australian universities, although there are few commonalities in its implementation. Given this diversity, it is important to consider how PELA practice can be understood, particularly in the light of language and literacy development. While there has been a strong movement towards embedded and discipline-specific language and literacy development in ALL practice, this has not been consistently applied to PELA practice. In Australian PELA practice, a number of fundamental and often unresolved questions persist concerning language and literacy development: who is responsible, how is it best enacted, and who is it for? This paper begins by reviewing the diversity of PELA practice in Australia, followed by a critical review of approaches that position PELA either outside of, or within, language and literacy development. The paper then presents two Western Australian university case studies and considers their work at the interface of PELA and embedded, discipline-specific language and literacy development practices. The paper argues for the need to move beyond a PELA-intervention cycle towards positioning PELA practice as an integral part of language and literacy development.